Atomic Scale Evolution of Graphitic Shells Growth via Pyrolysis of Cobalt Phthalocyanine. Issue 23 (9th September 2020) - Zhang, Xiaofang; Yang, Feng; Tian, Dongliang; Zhao, Haofei; Wang, Rongming; Lau, Woon‐Ming
Abstract: Nanostructured graphitic‐layer‐materials with precise control of the layer‐nanostructure, are known to surpass many benchmarks in electrical, optical, and mechanical properties. The development of such controlled synthesis is, however, stalled by the difficulty in tracking the exact growth mechanism and dynamics of the layer‐structure. Herein, the growth mechanism of onion‐like graphitic‐layer‐structures with an atomic precision is revealed by pyrolysis in an aberration‐corrected environmental transmission electron microscopy (ETEM). Specifically, the time‐evolution of cobalt phthalocyanine (CoPc), bearing better contact between carbon atoms and metamorphosizing a graphitization‐catalyst, at 850°C in an ETEM are tracked to an intriguing Co‐Co3 C nanocore enveloped by several graphitic layers. The growth dynamics of this onion‐like graphitic shell comprises, rather unexpectedly, out‐diffusion of carbon atoms from the core to fuel the growth of new outermost shell‐layers, plus lateral/inwards and intrashell/intershell diffusion of carbon atoms to amend shell‐defects. Thus, unusual dynamics of seemingly contracting shell‐expansion and shell‐consolidation is revealed, with the surprising phenomenon of a decrease in the number of atomic shell‐layers in exchange for layer‐perfectness towards the end of the controlled synthesis. These results indicate pyrolysis of an organometallic compound in an ETEM is a paradigm for understanding and developing controlled synthesis of novel high‐quality graphitic‐layer‐materials. Abstract : The growth mechanism of onion‐like graphitic‐layer‐structures with atomic precision is revealed by pyrolysis of cobalt phthalocyanine at 850 °C in an aberration‐corrected environmental transmission electron microscopy (ETEM), which indicates pyrolysis of an organometallic compound, bearing the dual roles of supplying carbon atoms and metamorphosizing a graphitization‐catalyst, in an ETEM is a paradigm for developing and understanding controlled synthesis of novel graphitic‐layer‐materials.